The Arabic Loan Words into Sasak Language. Study of Sasak Religious Leaders In Aikmel Sub-District, East Lombok - Dony Arizamri; Rika Astari (Indonesian Journal of Arabic Studies, 2023)
Purpose: This study investigates the integration of Arabic loanwords into the Sasak language in East Lombok's Aikmel sub-district, with a focus on the influence of the Salafi community. The aim is to analyze the implications of this linguistic phenomenon on the local Sasak-speaking community, particularly considering the Salafi community's impact. Design/ methods/approach: Employing a descriptive-qualitative approach, the research combines primary data from interviews and observations with secondary data analysis. The methodology involves organizing interview data and related information into thematic chapters, with an inductive exploration of Sasak-to-Arabic terminology and the environmental perspectives of group members. Findings: The investigation identifies 24 Arabic loanwords in the Sasak language, primarily attributed to the assimilation and Arabization efforts of the Salafis. The study finds that the incorporation of these loanwords notably enhances the understanding of divinity concepts among the Sasak Salafi community. This leads to improved comprehension of Arabic and a greater familiarity with Islamic terminology. Furthermore, the presence of Arabic loanwords has resulted in a linguistic shift, altering the grammatical structure and meaning of the Sasak language. Research implications: Â The research's significance lies in its examination of the dynamic interplay between language and religion. It highlights language's role as a medium for religious and cultural transmission, emphasizing the transformative impact of religious movements on local languages. These findings contribute to broader discussions on language evolution, cultural identity, and religious influence, offering valuable insights for linguists, cultural researchers, and religious scholars.